Approximate BER expressions for FSO communication systems with multiuser diversity - Abou-Rjeily, Chadi (2018)
This paper tackles the performance analysis of multiuser diversity (MD) free space optical (FSO) communication systems. In particular, we evaluate the performance of the n-th best user point-to-multipoint selection scheme and the performance of the multipoint-to-multipoint user grouping scheme. We derive approximate bit error rate (BER) expressions under lognormal and gamma-gamma scintillation. The approximation technique is based on the recurrence relations between the probability density functions (pdf's) of order statistics and on moment matching methods for deriving the parameters of the approximating pdf. Results highlight the accuracy of the derived expressions in predicting the BER performance.